2022
DOI: 10.3390/ijms23042161
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Highly Stable Silver NanoParticles as Novel Potential Antimicrobial Agents for Wound Healing Hydrogels

Abstract: Recurrent microbial infections are a major cause of surgical failure and morbidity. Wound healing strategies based on hydrogels have been proposed to provide at once a barrier against pathogen microbial colonization, as well as a favorable environment for tissue repair. Nevertheless, most biocompatible hydrogel materials are more bacteriostatic than antimicrobial materials, and lack specific action against pathogens. Silver-loaded polymeric nanocomposites have efficient and selective activity against pathogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…Therefore, the biopolymers are normally used for stabilization. For instance, the authors of [ 22 ] synthesized AgNPs in the presence of stabilizers in the form of polysaccharides, i.e., ulvan and cellulose. The AgNPs retained its stability even upon loading of a hyaluronic acid-based hydrogel.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the biopolymers are normally used for stabilization. For instance, the authors of [ 22 ] synthesized AgNPs in the presence of stabilizers in the form of polysaccharides, i.e., ulvan and cellulose. The AgNPs retained its stability even upon loading of a hyaluronic acid-based hydrogel.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 5a, Dizaj et al 67 concluded that the key factor to induce cell death is that NPs penetrate the cell membrane of bacteria and then destroy the key enzyme of bacteria. Figure 5b showed that the researchers loaded Ag NPs which were prepared by reducing silver nitrate with sodium borohydride into photo‐crosslinked hyaluronic acid methacrylate hydrogels, and it was an effective strategy for novel antibacterial hydrogel coatings 70 . Ag NPs achieved antibacterial purpose by inhibiting signal transduction 71 .…”
Section: The Function Of Hydrogel Coatingsmentioning
confidence: 99%
“…The most acceptable form of new wound dressings is BC nanomaterials with nanoscale inorganic particles. For this purpose, silver nanoparticles are included [ 194 , 195 , 196 , 197 ], and they have antimicrobial, anti-inflammatory and healing. Silver nanoparticles (AgNP) incorporated into the BC matrix imparts antibacterial properties to the composite through the release of silver ions affecting DNA replication, the breakdown of the cell membrane, and the release of reactive oxygen species [ 197 ].…”
Section: Bc-based Nanocompositesmentioning
confidence: 99%